Sn(ii, iv) steric and electronic structure effects enable self-selective doping on Fe/Si-sites of Li2FeSiO4 nanocrystals for high performance lithium ion batteries. Issue 48 (20th November 2015) - Wang, Kai; Teng, Gaofeng; Yang, Jinlong; Tan, Rui; Duan, Yandong; Zheng, Jiaxin; Pan, Feng
Abstract : Ab initio calculations reveal that the electrochemical performance improvement of Sn(ii, iv ) self-selective dual-doping of Li2 FeSiO4 is attributed to the enhanced electronic conductivity and lowered delithiation voltage. Abstract : We report Sn(ii ) and Sn(iv ) self-selective dual-doping, respectively, on Fe and Si sites of Li2 FeSiO4 nanocrystals due to the steric and electronic structure effects of Sn(ii, iv ). Combined with experimental studies and theoretical calculations, we investigate the structure–property relationship of tin doped Li2 FeSiO4 as the cathode material for high performance Li-ion batteries, in which the dual-doping enhances the electronic conductivity and lithium-ion diffusion coefficient. The doped sample with 5% Sn(iv ) source shows the best electrochemical performance due to the improved electronic conductivity and Li-ion diffusivity. Density functional theory (DFT) calculations also reveal that tin dual-doped Li2 FeSiO4 has better electronic conductivity and lower voltage of delithiation than that of the undoped Li2 FeSiO4, which is in accordance with our experimental results.